Evolution of technologies and equipment for feed mixture preparation – the basis for the research of economic efficiency of feed production - Кухта, Катерина Олексіївна (Technology audit and production reserves, 2013)
At the beginning of 1930 in Poltava, the experimental feed mill was put into operation with a capacity of 65 tons/day. The technological methods were worked out, the technologies were studied, and equipment was tested on this mill. Much attention was paid to the laboratory and technical base - incoming control of raw materials, toxicity issues, devices for the express analysis of raw materials and finished products. In the middle of the XX century, an integrated approach to the rational animal feeding was formed, which is based on the interaction of three conditions: preparation of nutritiousness- and quality-balanced feed ingredients, animal feeding in the necessary amount and organization of simultaneous feed intake of animal. The study of the content of nutrients in feeds and their matching to the needs of animals showed that none of feed materials of plant origin contains the necessary set of nutrients, needed for normal vital activity of animals. These data preceded the scientific development and application of multi-component rations, which fully satisfy the need for nutrients, that is feed mixtures. To study the efficiency of feed production, the evolution of technologies, from ancient technologies to modern mobile feed mills, was considered in the paper. The periodization of technologies and technical means of feed mixtures preparation is given in the paper, which allows to determine the patterns of the evolution of scientific and technical thought, and to predict further development of mechanization of feed production in accordance with changing conditions and needs of society.